Multilingual validation of the short form of the Unesp-Botucatu Feline Pain Scale (UFEPS-SF) - Luna, Stelio P.L. [UNESP]; Trindade, Pedro H.E. [UNESP]; Monteiro, Beatriz P.; Crosignani, Nadia; della Rocca, Giorgia; Ruel, Helene L.M.; Yamashita, Kazuto; Kronen, Peter; Te Tseng, Chia; Teixeira, Lívia [UNESP]; Steagall, Paulo V. [UNESP] (PeerJ, 2022)
Background. Pain is the leading cause of animal suffering, hence the importance of validated tools to ensure its appropriate evaluation and treatment. We aimed to test the psychometric properties of the short form of the Unesp-Botucatu Feline Pain Scale (UFEPS-SF) in eight languages. Methods. The original scale was condensed from ten to four items. The content validation was performed by five specialists in veterinary anesthesia and analgesia. The English version of the scale was translated and back-translated into Chinese, French, German, Italian, Japanese, Portuguese and Spanish by fluent English and native speaker translators. Videos of the perioperative period of 30 cats submitted to ovariohysterectomy (preoperative, after surgery, after rescue analgesia and 24 h after surgery) were randomly evaluated twice (one-month interval) by one evaluator for each language unaware of the pain condition. After watching each video, the evaluators scored the unidimensional, UFEPS-SF and Glasgow composite multidimensional feline pain scales. Statistical analyses were carried out using R software for intra and interobserver reliability, principal component analysis, criteria concurrent and predictive validities, construct validity, item-total correlation, internal consistency, specificity, sensitivity, the definition of the intervention score for rescue analgesia and diagnostic uncertainty zone, according to the receiver operating characteristic (ROC) curve. Results. UFEPS-SF intra- and inter-observer reliability were ≥0.92 and 0.84, respectively, for all observers. According to the principal component analysis, UFEPS-SF is a unidimensional scale. Concurrent criterion validity was confirmed by the high correlation between UFEPS-SF and all other scales (≥0.9). The total score and all items of UFEPS-SF increased after surgery (pain), decreased to baseline after analgesia and were intermediate at 24 h after surgery (moderate pain), confirming responsiveness and construct validity. Item total correlation of each item (0.68-0.83) confirmed that the items contributed homogeneously to the total score. Internal consistency was excellent (≥0.9) for all items. Both specificity (baseline) and sensitivity (after surgery) based on the Youden index was 99% (97-100%). The suggestive cut-off score for the administration of analgesia according to the ROC curve was ≥4 out of 12. The diagnostic uncertainty zone ranged from 3 to 4. The area under the curve of 0.99 indicated excellent discriminatory capacity of UFEPS-SF. Conclusions. The UFEPS-SF and its items, assessed by experienced evaluators, demonstrated very good repeatability and reproducibility, content, criterion and construct validities, item-total correlation, internal consistency, excellent sensitivity and specificity and a cut-off point indicating the need for rescue analgesia in Chinese, French, English, German, Italian, Japanese, Portuguese and Spanish.
Keywords: Analgesia; Animal welfare; Cats; Felidae; Feline; Pain; Pain scale; Postoperative care; Reliability; Validation study